2011
DOI: 10.1051/0004-6361/201014457
|View full text |Cite
|
Sign up to set email alerts
|

The period and amplitude changes in the coolest GW Virginis variable star (PG 1159-type) PG 0122+200

Abstract: Context. The PG 1159 pre-white dwarf stars experiment a rapidly cooling phase with a time scale of a few 10 6 years. Theoretical models predict that the neutrinos produced in their core should play a dominant role in the cooling, mainly at the cool end of the PG 1159 sequence. Measuring the evolutionary time scale of the coolest PG 1159 stars could offer a unique opportunity to empirically constrain the neutrino emission rate. Aims. A subgroup of the PG 1159 stars are nonradial pulsators, the GW Vir type of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The theoretical exploration of these mechanisms was extensively developed in Buchler et al (1995Buchler et al ( , 1997, but was almost interrupted more than a decade ago because of the lack of clear observational evidence of such phenomena, as a result of the difficulty in capturing amplitude or frequency variations that occur on timescales of months to years from ground-based observatories. Nevertheless, the presence of resonant couplings within rotationally split mode triplets was proposed for the first time as the explanation for the frequency and amplitude of longterm variations observed in the GW Vir pulsator PG 0122+200 (Vauclair et al 2011) from successive campaigns on this object. This suggests that pulsating white dwarfs could be among the best candidates to detect and test the nonlinear resonant coupling theory.…”
Section: Introductionmentioning
confidence: 94%
“…The theoretical exploration of these mechanisms was extensively developed in Buchler et al (1995Buchler et al ( , 1997, but was almost interrupted more than a decade ago because of the lack of clear observational evidence of such phenomena, as a result of the difficulty in capturing amplitude or frequency variations that occur on timescales of months to years from ground-based observatories. Nevertheless, the presence of resonant couplings within rotationally split mode triplets was proposed for the first time as the explanation for the frequency and amplitude of longterm variations observed in the GW Vir pulsator PG 0122+200 (Vauclair et al 2011) from successive campaigns on this object. This suggests that pulsating white dwarfs could be among the best candidates to detect and test the nonlinear resonant coupling theory.…”
Section: Introductionmentioning
confidence: 94%
“…Althaus et al (2008) have found that this discrepancy could be alleviated if PG1159−035 is characterized by a thin He-rich envelope, leading to remarkably large magnitudes of the rates of period change. A measurement ofΠ in another GW Vir star, PG0112+200, has been carried out by Vauclair et al (2011). The derived rates of period change are much larger than those predicted by theoretical models (Córsico et al 2007), calling for the presence of other mechanism(s) apart from neutrino cooling to explain the disagreement.…”
Section: Introductionmentioning
confidence: 98%
“…The derived rates of period change are much larger than those predicted by theoretical models (Córsico et al 2007), calling for the presence of other mechanism(s) apart from neutrino cooling to explain the disagreement. In particular, a mechanism that could be playing a dominant role is resonant mode coupling induced by the rotation (Vauclair et al 2011). A cautionary note regarding the interpretation of the measured rates of period change in pulsating WDs is needed here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, up to now it has been impossible to determine the rate of period change generated by secular cooling in DOVs or DBVs (Vauclair et al 2011;Chote et al 2013;Dalessio et al 2013), although some hints have recently been found by Redaelli et al (2011). Blinnikov & Dunina-Barkovskaya (1994) showed that the early WDLF of Fleming et al (1986) implied that the magnetic dipole moment is μ ν < ∼ 10 −11 μ B .…”
Section: Introductionmentioning
confidence: 99%